PENGARUH PERGANTIAN MANAJEMEN, UKURAN KAP, FINANCIAL DISTRESS, DAN PERTUMBUHAN PERUSAHAAN TERHADAP AUDITOR SWITCHING - Mazdina Dwi Astuty (2021)
This research is a quantitative study which aims to determine the effect of management change, size of KAP, financial distress , and company growth on auditor switching . This study uses data in the annual reports of manufacturing companies listed on the Indonesia Stock Exchange. The sample selection was carried out by using purposive sampling technique with predetermined criteria in order to obtain the amount of data 411 sample data from 137 companies. The test of this study used logistic regression analysis with the SPSS program and a significance level of 5% (0.05). The results of this study indicate that firm size and company growth have a negative effect on auditor switching , while management change and financial distress have no effect on auditor switching .